AGRICULTURAL CREDIT ACCESSIBILITY AND FINANCIAL INCLUSION AMONG RURAL FARMERS IN ORHIONMWON LOCAL GOVERNMENT AREA, EDO STATE, NIGERIA - Aigba, G.A.; Ighoro, A.; Okuonghae, O.F.; Ewekhare, B.T. (Nigerian Journal of Agriculture and Agricultural Technology, 2026)
The study examined agricultural credit accessibility and financial inclusion among rural farmers in Orhionmwon Local Government Area, Edo State, Nigeria. A multi-stage sampling procedure was employed to select 80 respondents. Data were collected using structured questionnaire and analysed using both descriptive and binary logistic regression analysis. Results show that only 36.25% of farmers accessed credit, with overwhelming reliance (87.5%) on informal sources. The Herfindahl-Hirschman Index analysis reveals a highly fragmented credit market with HHI values of 0.0000329 for processors and 0.0022862 for marketers. Logistic regression identifies short repayment periods as the most significant constraint (B = -1.539, p = .004), reducing credit access odds by 79%. While socio-economic factors like age, education, and gender showed limited statistical significance at the 0.05 alpha level of significance, institutional barriers including complex procedures and inadequate collateral emerged as critical impediments. The study concludes that credit access among farmers in Orhionmwon LGA is severely constrained, with only 36.25% accessing credit and 87.5% relying on informal sources. Short repayment periods constitute the most significant barrier, reducing credit access odds by 78.5% (p = 0.004). Institutional constraints dominate over individual socio-economic characteristics in determining access, with the model explaining 41% of variance and achieving 78.8% predictive accuracy.